2018
DOI: 10.1002/zamm.201700353
|View full text |Cite
|
Sign up to set email alerts
|

Towards non‐invasive in vivo characterization of the pathophysiological state and mechanical wall strength of the individual human AAA wall based on 4D ultrasound measurements

Abstract: Abdominal aortic aneurysms (AAA) are a degenerative disease of the aorta with high associated mortality. Currently, there is a lack of in vivo information, which allows to characterise the individual aneurysmal wall with regard to wall strength or rupture risk. We have used 4D ultrasound strain imaging to compute the spatially resolved distribution of the in-plane strain tensor and of the local distensibility in three patient groups (young, < 40 y. o.; elderly, > 60 y. o.; AAA). Mean and local maximum deformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 88 publications
(119 reference statements)
1
28
0
Order By: Relevance
“…The cyclic registration of strain amplitude of all speckles with the temporal resolution of 22–26 frames/s enabled the precise definition of diastolic and systolic aortic diameters and patient‐specific strain. The circumferential strain was chosen as the most significant parameter for the investigation of 4D‐US reliability 8,7 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The cyclic registration of strain amplitude of all speckles with the temporal resolution of 22–26 frames/s enabled the precise definition of diastolic and systolic aortic diameters and patient‐specific strain. The circumferential strain was chosen as the most significant parameter for the investigation of 4D‐US reliability 8,7 …”
Section: Methodsmentioning
confidence: 99%
“…However, the introduction of real‐time 3D speckle‐tracking ultrasound (4D‐US) enables the imaging of the entire aortic segment and thus the simultaneous determination of the longitudinal and circumferential expansion 5 . In comparative studies, the age‐related and pathology‐specific changes in the strain pattern in the infrarenal aorta were demonstrated 6 and characterized by corresponding changes in distensibility 7 . The use of 4D‐US provides information about the geometry of the aorta and local deformation of the aortic wall during the heart cycle.…”
Section: Introductionmentioning
confidence: 99%
“…Abdominal aortic aneurysm (AAA) is an irreversible expansion of the infra-renal aorta at least 1.5 times of a healthy aortic diameter. In light of its high mortality rate, this condition is becoming one of the leading causes of death worldwide [1][2][3]. The current clinical guidelines consider only the maximum transverse diameter (D max ) of AAA (5.5 cm for men, and 5 cm for women) to monitor abdominal aortic aneurysm (AAA) severity, risk of rupture, and need for repair [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that in addition to geometric indices such as D max , a variety of biomechanical parameters and material properties affect AAA morphology and behavior [3,[7][8][9]. Wall stress distribution and mainly the peak wall stress -which is directly related to the failure site on the AAA surface -computed using finite element analysis (FEA) have been helpful to comprehensively consider the effects of all mentioned parameters [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The application of such computational modeling in a clinical context requires, of course, patient‐specific information about the mechanical properties of aneurysmal tissue. The paper [] points out in detail how such information can be obtained non‐invasively and at an acceptable cost by means of ultrasound techniques. Not only cardiovascular diseases but also cancer biomechanics have great promise as a source of ideas for future optimized treatments.…”
mentioning
confidence: 99%